Potency of Karamunting (Rhodomyrtus tomentosa) Leaf Extract as Antidiabetic for Type 2 Diabetes: A Systematic Review - Sutandar, Vivi Hendra; Saleh, M. Irsan; Lusiana, Evi; Parisa, Nita; Tamzil, Nia Savitri (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Type 2 diabetes mellitus (T2D) is a chronic metabolic disorder characterized by reduced insulin sensitivity and inadequate insulin secretion, leading to elevated blood glucose levels. Standard treatment relies on synthetic drugs, which can cause adverse effects in some patients. Rhodomyrtus tomentosa, a plant native to Indonesia and widely used in traditional medicine, is being explored as a natural alternative for diabetes management due to its potential antidiabetic properties. This review compiles recent findings on its therapeutic potential. A systematic literature search was conducted in August 2024 in PubMed, Wiley Online Library, ScienceDirect, Cochrane Library, ProQuest, and Google Scholar using the keywords “Rhodomyrtus tomentosa” and “antidiabetic.” Of 774 screened articles, five met the inclusion criteria (2014–2024). The studies employed in vitro, in vivo, and in silico approaches, focusing mainly on fruits and leaves. Results indicate that R. tomentosa may help control blood glucose by inhibiting α-glucosidase and α-amylase, enzymes critical in carbohydrate digestion. Bioactive compounds such as phloroglucinols and meroterpenes were frequently identified. However, most evidence comes from laboratory models, with limited animal research and no clinical trials. The risk of bias was moderate, often due to incomplete reporting. While findings suggest R. tomentosa is a promising natural candidate for diabetes treatment, its therapeutic value remains unconfirmed. More robust in vivo studies and human clinical trials are essential to clarify its mechanisms, safety, pharmacokinetics, and efficacy. This review serves as a basis for future research and highlights the need for rigorous studies to validate its clinical potential.